Legal Reconstruction of the Omnibus Law on Job Creation for Justice in Enhancing Investment and Indonesia’s Competitiveness - Hendra Gunawan; Syahbudin Syahbudin (Jurnal Hukum, 2025)
The Omnibus Law on Job Creation (Law No. 11 of 2020 as amended by Law Number 6 of 2023) is a key Indonesian government policy designed to boost investment and national competitiveness by simplifying the investment ecosystem and enhancing the ease of doing business. This study examines the need for legal reconstruction of the law to create a more equitable regulatory framework that promotes investment, competitiveness, legal certainty, and labor protection. Despite Indonesia’s strong appeal to foreign investors, challenges such as bureaucratic inefficiencies, corruption, and legal uncertainty persist. While the Omnibus Law aims to improve regulatory efficiency, its implementation has been criticized, particularly by labor groups who argue that it prioritizes capital over worker welfare. Furthermore, inefficiencies in investment management are highlighted by the high Incremental Capital Output Ratio (ICOR), indicating that large investments are not yielding expected economic returns. This study proposes strategies for legal reform to address labor concerns, improve legal transparency, and enhance infrastructure, with the goal of optimizing the policy’s impact on sustainable economic growth. The research aims to contribute to the development of a more balanced legal framework that supports both economic progress and social welfare.